ERROR ANALYSIS ON THE STUDENTS WRITING OF SIMPLE PRESENT TENSE IN A DESCRIPTIVE TEXT - Bara Vera; Acep Haryudin; Windy Herdiyanti (PROJECT (Professional Journal of English Education), 2019)
One of English skills which is important to be mastered by the students’ is writing skill. Writing is a creative and expressive process. Students need to explore their ideas and compose into a good text. The objectives of this research is to find out types of error and the most dominant error writing using simple present tenses in a descriptive text made by the seventh grade students of MTs Asih Putera. The research design is qualitative design. The data were gathered from students’ test as a document analysis. Then, the researcher analyzed, classifying errors the students’ work based on types of errors by Dulay (1982). For calcuting the data, the researcher used one formula to know percentages errors. The result of this research, showed that there are 73 items of errors which occur in students’ sentence. It is found that 42 items or 57,53% errors are omission, 10 items or 13,70% are addition, 16 items or 21,92% are misformation, and 5 items or 6,85% are disordering. The conclusion based on the research result data, most student were made error in using simple present tense in a descriptive text, especially was ommision errors.